Affirmative Action Untuk Penyandang Disabilitas: Memenuhi Hak Pilih dalam Pemilu Yang Adil - Razak, Askari (Wajah Hukum, 2023)
This research analyzes the fulfillment of voting rights for people with disabilities in elections and the efforts of affirmative action to achieve justice. People with disabilities have equal opportunities in elections according to the Constitutional Court's decision and the Election Law. Although the number of people with disabilities is approximately 1% of the population, it is important for the General Election Commission (KPU) to accurately register them. The fulfillment of voting rights for people with disabilities is in accordance with the 1945 Constitution and the Human Rights Law. People with disabilities are vulnerable groups with special rights guaranteed by the Disability Law. However, their political rights are often neglected due to stigma and discrimination. Through normative legal research, affirmative action becomes important as a temporary policy to provide equal opportunities. Active participation of people with disabilities is key in elections. The government categorizes voters as normal and those with mental disorders, but the difference between mental disabilities and insanity must be understood. Mental disorders and memory impairment are not the only requirements for elections. This research emphasizes the importance of fulfilling the voting rights of people with disabilities and the efforts of affirmative action for justice. Improvements in registration systems, elimination of stigma, and better understanding of political rights are expected to increase participation in the political process.